The dehydrogenase region of the NADPH oxidase component Nox2 acts as a protein disulfide isomerase (PDI) resembling PDIA3 with a role in the binding of the activator protein p67phox - Bechor, Edna; Dahan, Iris; Fradin, Tanya; Berdichevsky, Yevgeny; Zahavi, Anat; Federman Gross, Aya; Rafalowski, Meirav; Pick, Edgar (Frontiers in Chemistry, 2015)
The superoxide (O2.-)-generating NADPH oxidase of phagocytes consists of a membrane component, cytochrome b558 (a heterodimer of Nox2 and p22phox), and four cytosolic components, p47phox, p67phox, p40phox, and Rac. The catalytic component, responsible for O2.- generation, is Nox2. It is activated by the interaction of the dehydrogenase region (DHR) of Nox2 with the cytosolic components, principally with p67phox. Using a peptide-protein binding assay, we found that Nox2 peptides containing a 369CysGlyCys371 triad (CGC) bound p67phox with high affinity, dependent upon the establishment of a disulfide bond between the two cysteines. Serially truncated recombinant Nox2 DHR proteins bound p67phox only when they comprised the CGC triad. CGC resembles the catalytic motif (CGHC) of protein disulfide isomerases (PDIs). This led to the hypothesis that Nox2 establishes disulfide bonds with p67phox via a thiol-dilsulfide exchange reaction and, thus, functions as a PDI. Evidence for this was provided by the following: 1. Recombinant Nox2 protein, which contained the CGC triad, exhibited PDI-like disulfide reductase activity; 2. Truncation of Nox2 C-terminal to the CGC triad or mutating C369 and C371 to R, resulted in loss of PDI activity; 3. Comparison of the sequence of the DHR of Nox2 with PDI family members revealed three small regions of homology with PDIA3; 4. Two monoclonal anti-Nox2 antibodies, with epitopes corresponding to regions of Nox2/PDIA3 homology, reacted with PDIA3 but not with PDIA1; 5. A polyclonal anti-PDIA3 (but not an anti-PDIA1) antibody reacted with Nox2; 6. p67phox, in which all cysteines were mutated to serines, lost its ability to bind to a Nox2 peptide containing the CGC triad and had an impaired capacity to support oxidase activity in vitro. We propose a model of oxidase assembly in which binding of p67phox to Nox2 via disulfide bonds, by virtue of the intrinsic PDI activity of Nox2, stabilizes the primary interaction between the two components.